Combination antiretroviral therapy reduces the detection risk of cervical human papilloma virus infection in women living with HIV. (2nd January 2015) - Zeier, Michèle D.; Botha, Matthys H.; Engelbrecht, Susan; Machekano, Rhoderick N.; Jacobs, Graeme B.; Isaacs, Shahieda; van Schalkwyk, Marije; van der Merwe, Haynes; Mason, Deidre; Nachega, Jean B.
Abstract : Objective: Data on the effect of combination antiretroviral therapy (cART) on cervical human papilloma virus (HPV) infection are both limited and conflicting. We aimed to determine the effect of the initiation of cART for HPV genotype detection on cervical samples in HIV-infected South African women. Design: Prospective cohort study. Methods: Generalized estimating equation was performed to estimate parameters of mixed-effects logistic regression models of cART on HPV cervical detection risk, adjusting for time-dependent covariates CD4 + T-cell count, sexual activity and excision treatment. Ratio of odds ratios (ORs) was computed to compare the pooled cART effect on lower vs. high-risk HPV genotype groups, to the effect of cART on the risk of HPV-16 detection. Results: Of the 300 patients, 204 (68%) were commenced on ART during follow-up, as they met the criteria for cART initiation. cART significantly reduced the risk for detection of HPV by 77% [OR 0.23, 95% confidence interval (CI) 0.15–0.37]. cART significantly reduced the risk of HPV-16 detection (OR 0.50, 95% CI 0.37–0.67). Every month on cART significantly reduced the detection risk of any HPV type by 9% (OR 0.91, 95% CI 0.89–0.94). The protective effect of cART on the detection risk for the low-risk HPV genotype group was significantly less than the protective effect of cART on the detection risk of HPV-16 (ratio of ORs 1.35, 95% CI 1.22–1.50). Conclusion: cART significantly reduced cervical HPV infection. This effect was dependent on the duration of exposure to cART and is the mechanism by which cART may improve the outcome of dysplasia in HIV-infected women.